DEMOCRATIC FRAGILITY IN THE ERA OF LIQUID EXCEPTION: REFLECTIONS OF MONTESQUIEU’S THEORY IN BRAZIL - de Sousa Ramos, Anaelisa (Revista Gênero e Interdisciplinaridade, 2026)
The work examines the impact of the Liquid State of Exception, a contemporary concept based on Bauman, on democracies, especially in Brazil, analyzing how it affects the separation of powers and the fundamental freedoms defended by Montesquieu. The concept, more diffuse than the classic one, allows the three branches of government to expand their authority in the name of their interests. The research utilizes a literature review based on Bauman’s “Liquid Modernity” (2000) and Montesquieu’s “The Spirit of the Laws” (1748), in addition to contemporary studies, such as those by Agamben (2003) on the State of Exception. The analysis focuses on the actions of the evangelical caucus in the Brazilian National Congress and its attempts to limit religious freedom, correlating this phenomenon with the erosion of the separation of powers and the advance of the Liquid State of Exception. It is observed that the Liquid State of Exception threatens fundamental rights, weakening the system of checks and balances and compromising Brazilian democracy, especially regarding the religious freedom of religions of African origin. Montesquieu offers theoretical tools to resist this fluidity.